Characteristic of Tinea Cruris and/or Tinea Corporis in Ciamis District Hospital, West Java - Wulan Yuwita; Lies Marlysa Ramali; Risa Miliawati N. H. (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Tinea cruris and/or corporis is one of the most common dermatophytosis in the world, which is still being a health problem in Indonesia. Purpose: The purpose of this study was to find out the characteristic of tinea cruris and/or tinea corporis in Ciamis District Hospital, West Java. Methods: The design was descriptive cross-sectional study, with consecutive sampling methods. The subjects of the study were patients with tinea cruris and/tinea corporis who visited Dermatovenereology Clinic in Ciamis District Hospital, West Java. Data was collected from the history taking, physical examination, microscopic examination from skin scraping using 10% potassium hydroxide solution (KOH), and fungal culture, until 40 patients with positive result of dermatophyte culture were included. The study was conducted from 2015, 1st August to 15th October. Results: Tinea cruris and/or corporis were most commonly found in female (52.5%), age 45-64 years. Duration of illness £1 month (20/40), recurrence(7/40), the source of infection was anthropophylic (10/40), with clinical manifestations were erythematous and hyperpygmented macules and papules, scales, with central clearing (36/40). The most commonly isolated dermatophytes were Trichophyton rubrum (95.8%) followed by Epidermophyton floccosum (4.2%). Conclusion: The most frequent dermatophytes species causing tinea cruris and/or corporis in Ciamis District Hospital, West Java are T. rubrum followed by E. floccosum with minimal inflammation clinical manifestation and source of infection was antropophilic. Key words: tinea cruris, tinea corporis, Ciamis District Hospital.